Damaged goods? An Interpretative Phenomenological Analysis of the lived experience of women with inflammatory bowel disease in the UK - Murphy, Rachel (2023)
Just after I turned 50, I was diagnosed with the incurable inflammatory bowel condition of Crohn’s disease. The debilitating, stigmatising symptoms left me struggling to understand my new reality and sense of self. I searched for the experience of others to support my life readjustment but found most of the research concentrated on the somatic experience. There appeared to be little research into the impact of my illness on self-identity. I wondered how many women struggled with their illness identity, and whether they had found successful ways of living. This led to my decision to research and give voice to women living with inflammatory bowel disease (IBD). This research is significant as it uniquely considers the interrelated impact of IBD somatic symptoms, the resulting emotions, and women’s self-concept, on successfully finding a way to live. This research has an interpretative, critical paradigm, a humanistic, feminist theoretical framework, a social constructivist conceptual framework and a phenomenological epistemology (Creswell, 2007; Harding, 1987; Lincoln et al., 2018). The theoretical framework outlines the existing theory within which this research is situated and the conceptual framework outlines how the research question has been examined. The research methodology of Interpretative phenomenological Analysis was chosen to really understand the lived experience of women living with IBD (Smith and Nizza, 2022). Semi-structured interviews were conducted with 16 women and the resulting co-created data was analysed using the Stevick-Colaizzi-Keen method (Moustakas, 1994). The results were arranged into four group experiential themes of: wearing the straitjacket of illness; psychologically difficult emotions; flexibility of self; and navigating a way through. These themes led to the development of a model of post-traumatic illness survival, which encompasses illness experiences and prizes women who live with IBD. This new model can support women living with IBD and the healthcare professionals who help them to contextualise their path towards gaining greater flexibility of self. This in turn can promote individual ways of living that can ease the strain of life with this chronic condition. The model does not however, have an expectation of ‘growth’ due to illness. Instead, it celebrates the multitude of ways women survive in the face of such a debilitating condition.